Anaplastic Meningioma: A Rare Case Report - Gupta, Sumiti; Ankush; Goel, Vibhav; Dahiya, Mahak; Singh, Sunita (Annals of Pathology and Laboratory Medicine, 2025)
Meningiomas are tumors arising from the leptomeninges. The malignant counterpart of them is known as anaplastic meningioma, which are WHO grade 3 tumors. Histopathology and immunohistochemistry are confirmatory for subtyping of meningioma. We present a case of a 45-year-old male who presented with usual symptoms of headache and projectile vomiting. After surgery, the clinical diagnosis of meningioma was made, and the tissue was sent to the pathology department. Definitive diagnosis revealed a high-grade spindle cell neoplasm disposed in sheets with markedly elevated and atypical mitoses. Large cells with eccentric cytoplasm were also seen. IHC was positive for vimentin and EMA and negative for GFAP. A final diagnosis of anaplastic meningioma was made. During follow-up, the patient also received adjuvant radiotherapy post-surgery. Anaplastic meningioma is very rare and generally known to have a poorer prognosis. The extent of resection is associated with prognosis of patients with all WHO grades of meningioma.